ANALYSIS OF COST AND TIME VARIANCE IN CONSTRUCTION PROJECTS USING CV AND SV PARAMETERS: A CASE STUDY OF THE JEMBER LUNG HOSPITAL BUILDING - Widyarso, Riza; Witjaksana, Budi; Purnama, Jaka (International Journal of Social Service and Research, 2025)
Cost and time management in construction projects is an important aspect of project management. In this study, the cost and time performance of the Jember Lung Hospital Building construction project is evaluated using Schedule Variance and Cost Variance analysis. The study aims to provide practical and applicable solutions to improve time and cost efficiency without sacrificing project quality. The results show that the project experienced a cumulative delay of 29 calendar days and considerable cost overruns compared to the original budget. In addition, the study focuses on analyzing the effectiveness of CV and SV variance analysis in the context of construction projects in Indonesia. The findings highlight the importance of strengthening risk management, more careful planning, and the application of more advanced project management technologies to improve the efficiency and sustainability of future projects.